Vectors and Vector-Borne Zoonotic Diseases - Savić, Sara (IntechOpen, 2019)
Vectors and Vector-Borne Zoonotic Diseases is about a group of diseases that can infect humans and animals, and that are transmitted by vectors. These diseases are called vector-borne zoonotic diseases. This book is meant to be used by veterinarians, medical doctors, entomologists, and other experts, as well as students, animal owners, nature lovers, etc. The book has several sections: "Introduction," "Vectors", "Vector-Borne Diseases and Pathogens," and "Vector Control." Each of the sections concerns one stage of a vector-borne disease. Each group of authors has dedicated their work to one of the topics with key roles on pathogens or vectors that are of great public health interest in their country or region. In this book, the authors have tried to show which vectors and diseases are the most interesting, having in mind that their spreading represents a danger to health. With this book, we hope to broaden readers' knowledge by sharing experiences with vector-borne diseases,with the aim to upgrade the knowledge of general public health from a One Health perspective.